INCIDENCE OF INTRA VENTRICULAR HEMORRHAGE IN PRETERM NEWBORNS AT SIR GANGA RAM HOSPITAL, LAHORE (Journal of Medical & Health Sciences Review, 2025)
Background: Intraventricular hemorrhage (IVH) remains a serious complication in preterm infants, particularly those born with low birth weight or reduced gestational age. It is a major contributor to neonatal illness and death, especially in resource-limited regions such as Pakistan, where information on its prevalence and contributing factors is still scarce.Objective: To determine the incidence of IVH in preterm newborns admitted to Sir Ganga Ram Hospital, LahoreMethods: This prospective observational cross-sectional study was conducted at the Department of Pediatrics, Sir Ganga Ram Hospital from 15 September 2024 to 15 March 2025. A total of 81 preterm neonates (aged 0–28 days) were enrolled through non-probability consecutive sampling. Cranial ultrasounds were performed within the first week of life and reported by a consultant radiologist. Data were analyzed using SPSS v20.0 with stratification and chi-square tests.Results: The overall incidence of IVH was 25.9%. A significantly higher incidence was observed among neonates